Sport as a tourism attraction in Malaysia: potential and prospects - Jabil Mapjabil,; Mazdi Marzuki,; Mohd Jirey Kumalah,; Logeswaran Tangavello,; Mohammad Kadir Zainal Abidin, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Sport tourism has become a popular sub-sector in the tourism industry today. Until the early 1990s, tourism and sports existed as two distinct areas of activities but the success in organizing the World Conference on Sport Tourism in Barcelona, Spain 2001has resulted in more serious attention being paid to this sector. Before, scholars, decisionmakers and governments involved in the field of tourism and sports perceived their respective profits independently of one another; now it is realised that the benefits generated by the synergy of both is far greater. This study examines the development of sport tourism in Malaysia. It was found that the success in organizing the race Le Tour de Langkawi in 1996 was a turning point in the government's focus on the development of the sport tourism sector. Currently, Malaysia is known for organizing several world-class sport events, among them the Royal Langkawi International Regatta (January), Ironman Triathlon (February), Formula 1 Grand Prix Malaysia (March), FEI Showjumping World Cup (May), Petronas Primax 3 Merdeka Millennium Endurance Race (July), Super GT (August), Malaysian Motorcycle Grand Prix (September), A1GP Malaysia (November) and Monsoon Cup (December). All these world-class sporting events bring substantial returns to the society and the economy. The strengths of sports as a tourism attraction include the length of time in which the events take place, extensive publicity coverage through the print and electronic media, sponsorship from various domestic and multinational companies and business opportunities provided to local residents during the event.